Connecting Women's Histories: the local and the global. Issue 4 (3rd July 2016) - Bush, Barbara; Purvis, June
ABSTRACT: The articles in this Special Issue are drawn from some of the contributions to a conference held at Sheffield Hallam University, UK, from 29 August to 1 September 2013 titled 'Women's Histories: the local and the global'. The articles reflect on diverse aspects of the entangled histories of women across the world, mainly, but not exclusively, during the twentieth century. They explore the range of ways in which women's history, international history, transnational history and imperial and global histories are interwoven.